1995
DOI: 10.1128/aem.61.12.4471-4473.1995
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Vegetative Catalase Is an Extracellular Enzyme

Abstract: Strong catalase activity was secreted by Bacillus subtilis cells during stationary growth phase in rich medium but not in sporulation-inducing medium. N-terminal sequencing indicated that the secreted activity was due to the vegetative catalase KatA, previously considered an endocellular enzyme. Extracellular catalase protected B. subtilis cells from oxidative assault. The molecular response to oxidative stress has been extensively studied as it occurs in both gram-negative (6, 17) and gram-positive (18) bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Subcellular localization of the catalase protein. Although many of the well-characterized bacterial catalases are typically present in the cytoplasm, some, such as the KatA catalase from B. subtilis (8,29), are exported. Because the V. fischeri enzyme has a high degree of identity with the B. subtilis catalase, and because a secreted catalase might be of particular value if the light organ environment were a significant source of reactive oxygen species, we investigated whether the catalase protein from V. fischeri was exported.…”
Section: Resultsmentioning
confidence: 99%
“…Subcellular localization of the catalase protein. Although many of the well-characterized bacterial catalases are typically present in the cytoplasm, some, such as the KatA catalase from B. subtilis (8,29), are exported. Because the V. fischeri enzyme has a high degree of identity with the B. subtilis catalase, and because a secreted catalase might be of particular value if the light organ environment were a significant source of reactive oxygen species, we investigated whether the catalase protein from V. fischeri was exported.…”
Section: Resultsmentioning
confidence: 99%
“…This catalase appears to be synthesized throughout growth, since both exponential-phase and longterm-starved culture supernatants conferred resistance to hydrogen peroxide. Such an extracellular catalase has been identified in Bacillus subtilis and was found to protect cells from a hydrogen peroxide challenge (28).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins involved in metabolism of amino acids, RocA and RocF, were initially found by Antelman et al [ 20 ] to be non-classically secreted, but only RocF was later identified by Vitikainen et al [ 19 ]. The vegetative catalase KatA that was previously considered to be an intracellular enzyme due to the absence of a signal peptide, was later found to be localized extracellularly when B. subtilis was grown in the rich medium (about 56 % of the total KatA) [ 21 ]. Of course, the detection of non-classically secreted proteins in the extracellular environment could obviously be attributed to cell lysis.…”
Section: Introductionmentioning
confidence: 99%